Ebony and the Mascarenes: the evolutionary relationships and biogeography of Diospyros (Ebenaceae) in the western Indian Ocean. (10th July 2019) - Linan, Alexander G; Schatz, George E; Lowry, Porter P; Miller, Allison; Edwards, Christine E
Abstract: Using analyses that exhaustively sampled Mascarene Diospyros and included representative taxa from Madagascar and other regions, we explored: (1) evolutionary relationships among Diospyros spp. across the WIO and (2) biogeographic connections of Malagasy taxa with those in surrounding regions, particularly focusing on connections with taxa in the Mascarene Islands. We obtained plastid sequence data for 146 Diospyros taxa, including 40 species not previously included in molecular analyses, and conducted Bayesian and maximum-likelihood phylogenetic analyses, divergence-time estimation and ancestral area reconstructions. Diospyros sampled from Madagascar fell into two clades, one of which contains all but two Malagasy species. Biogeographic analyses revealed that many clades probably originated in Madagascar and dispersed to locations in Africa and the Mascarenes, indicating that Madagascar may have acted as an important source of diversity for the region.